ANALISIS FAKTOR YANG MEMPENGARUHI RISIKO SERANGAN JANTUNG PADA PENDERITA KOLESTEROL DI PUSKESMAS PAJARAKAN PROBOLINGGO - Nadliroh Fikri Ayu Ningtyas; Achmad Kusyairi; Ainul Yaqin salam (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Heart attack is an event caused by the blockage of coronary artery blood flow, resulting in insufficient oxygen supply to the heart muscle and leading to infarction, thereby suddenly interrupting the oxygen-rich blood supply to the heart. The purpose of this study was to determine the factors influencing the risk of heart attack among cholesterol patients at Puskesmas Pajarakan.This research used an analytic correlational design with a cross-sectional approach. The population consisted of 90 individuals, with a sample of 73 respondents selected using simple random sampling on May 25-27, 2025, based on inclusion and exclusion criteria. The research instrument utilized a questionnaire.Data obtained were analyzed bivariately using the Spearman’s Rank test and logistic regression to identify the dominant influencing factors. The results showed that smoking behavior (p=0.023), diabetes mellitus (p=0.039), and physical activity (p=0.594) were variables examined. The findings indicate significant correlation between smoking behavior with a wald value 6,082 and diabetes mellitus with a wald value 0,014. The dominant factor influencing the risk of heart attack was smoking behavior, with a Wald value of 6.082.In conclusion, respondents with smoking habits need to be proactive in managing their health conditions to reduce the risk of complications. Adopting a healthy lifestyle is crucial, including maintaining controlled blood sugar and cholesterol levels, managing blood pressure, quitting smoking, and engaging in regular physical activity.